Answers

2015-06-06T10:57:55+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
I am not sure if there is a shorter way in solving this one, but I can show you a solution only that it is a bit longer though.

Overview:
                       24                           3   

Formula:
              t_{n} =  t_{1} + (n-1) d
We will focus first in:   24                           3   
To find d:
Substitute:
                t_{n} for 3
                t_{1} for 24
                n for 4 
 3 = 24 + ( 4 -1 )d
 3 = 24 + 3d
 3 - 24 = 3d
 -21 = 3d
  - 21 / 3 = 3d /3
 -7 = d
We already have d = -7, we will go back to the original one.
             24                           3   

   t_{n} = t_{1} + (n-1) d
Substitute:

3 =  t_{1} + (5 - 1) -7
3 =  t_{1} + -28
3 =  t_{1} - 28
3 + 28 =  t_{1}
31 =  t_{1}
                
So, the common difference (d) is -7, while the first term ( t_{1} ) is 31
2 3 2
Thank you jeremia it will help me a lot :)
2015-06-06T22:32:17+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
a_5-a_2=(5-2)d \\ 3-24=3d \\ -21=3d \\ -7=d
We now have the common difference so:
a_n=a_1+(n-1)d \\ a_2=a_1+d \\ 24=a_1-7 \\ 31=a_1
1 4 1